Embolia cutis Medicamentosa (Nicolau syndrome): case series - Gyula Laszlo Fekete; Gyula Laszlo Fekete; Laszlo Barna Iantovics; Júlia Edit Fekete; Laszlo Fekete; Laszlo Fekete (Frontiers in Medicine, 2023)
IntroductionEmbolia cutis medicamentosa or Nicolau syndrome is a rare drug reaction associated with the administration of various injectable medications. The pathogenesis of the disease is unknown, though intra and periarterial injection of the drug is a possible cause. The aim of this study was to describe and analyze the clinical characteristics of Nicolau syndrome in patients examined in daily dermatological practice.MethodsWe performed a retrospective chart review, between January 2011 and December 2020, in patients diagnosed with Nicolau syndrome, from the cases of a private dermatology medical office in Târgu Mureș, Romania.ResultsDuring the 10-year period, 7 patients were diagnosed with Nicolau syndrome. Of these, 4 (57%) patients were males and 3 (43%) were females, The male to female ratio was 1.33. The median age was 64 (interquartile range, IQR, 62–71), with the youngest patient being diagnosed at age 61 and the oldest at age 74. Regarding the drugs classes that caused Nicolau syndrome, these were intravenous antibiotics in 57%, and non-steroidal anti-inflammatory drugs in 43% of cases.ConclusionAll patients healed in a period of 6 to 8 weeks. No complications occurred. In conclusion, Nicolau syndrome is a rare side effect of injectable drug administration.